The National Model for Managing Innovation in the Mining Industry: Theory and Practice (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper explores the development of a national model for managing innovation in Uzbekistan’s mining industry, integrating theoretical foundations with recent practical initiatives. In 2025, Uzbekistan announced a US$2.6 billion programme covering 76 projects related to 28 rare minerals aimed at strengthening the full value chain—from exploration to high-value processing—by investing in modern laboratories, technology transfer, and workforce capacity building [1]. Concurrently, partnerships with foreign companies (for example Orano) in uranium extraction and pilot investments in greener extraction methodologies have emerged as critical components of innovation practice in the sector [2]. The study employs mixed methods: analysis of policy documents, national sector statistics, case studies of major mining corporations, and qualitative interviews with innovation managers. The theoretical basis draws on national innovation systems theory, technology diffusion and value-chain integration models. Key findings suggest that legal reforms, rare minerals strategy, investment incentives, and digital transformation are central pillars of the national model. However, there are gaps: technology adoption remains uneven; many projects are in early pilot stages; financing for R&D and environmental compliance is limited; standards consistency and monitoring require strengthening.